Transperitoneal vs retroperitoneal laparoscopic radical nephrectomy: a double-arm, parallel-group randomized clinical trial - Junyao Liu; Bin Zhang; Peng Qi; Xiaowei Ren; Duo Zheng; Yang He; Xu Zheng; Zhongjin Yue; Ye Li; Ningqiang Yang; Zhiping Wang; Junsheng Bao; et al. (BMC Urology, 2024)
Abstract Objective To compare the outcomes of patients undergoing Retroperitoneal laparoscopic Radical nephrectomy (RLRN) and Transperitoneal laparoscopic Radical nephrectomy (TLRN). Methods A total of 120 patients with localized renal cell carcinoma were randomized into either RLRN or TLRN group. Mainly by comparing the patient perioperative related data, surgical specimen integrity, pathological results and tumor results. Results Each group comprised 60 patients. The two group were equivalent in terms of perioperative and pathological outcomes. The mean integrity score was significantly lower in the RLRN group than TLRN group. With a median follow-up of 36.4 months after the operation, Kaplan–Meier survival analysis showed no significant difference between RLRN and TLRN in overall survival (89.8% vs. 88.5%; P = 0.898), recurrence-free survival (77.9% vs. 87.7%; P = 0.180), and cancer-specific survival (91.4% vs. 98.3%; P = 0.153). In clinical T2 subgroup, the recurrence rate and recurrence-free survival in the RLRN group was significantly worse than that in the TLRN group (43.2% vs. 76.7%, P = 0.046). Univariate and multivariate COX regression analysis showed that RLRN (HR: 3.35; 95%CI: 1.12–10.03; P = 0.030), male (HR: 4.01; 95%CI: 1.07–14.99; P = 0.039) and tumor size (HR: 1.23; 95%CI: 1.01–1.51; P = 0.042) were independent risk factor for recurrence-free survival. Conclusions Our study showed that although RLRN versus TLRN had roughly similar efficacy, TLRN outperformed RLRN in terms of surgical specimen integrity. TLRN was also significantly better than RLRN in controlling tumor recurrence for clinical T2 and above cases. Trial registration Chinese Clinical Trial Registry ( https://www.chictr.org.cn/showproj.html?proj=24400 ), identifier: ChiCTR1800014431, date: 13/01/2018.